Is adjuvant chemotherapy beneficial for patients with FIGO stage IC adult granulosa cell tumor of the ovary? - Dan Wang; Yang Xiang; Ming Wu; Keng Shen; Jiaxin Yang; Huifang Huang; Tong Ren (BMC, 2018)
Abstract Background To evaluate the association between adjuvant chemotherapy and clinical outcomes in patients with stage IC adult granulosa cell tumor (AGCT). Methods We performed a retrospective study of patients with stage IC AGCT diagnosed at our hospital from January 1985 to September 2015. We analyzed descriptive statistics, and performed univariate and multivariate and Kaplan-Meier survival analyses. Results Sixty stage IC AGCT patients were identified, including 28 in the no adjuvant chemotherapy group (NACG) and 32 in the adjuvant chemotherapy group (ACG). The median follow-up time was 88 months (range: 9-334 months). Sixteen patients developed recurrences, including nine in the NACG and seven in the ACG groups. Univariate analysis identified incomplete surgical staging and initial treatment place as associated with disease-free survival (DFS) (P = 0.003 and 0.038, respectively). Incomplete surgical staging remained a risk factor for recurrence in multivariate analysis (hazard ratio (HR) = 3.883, 95% confidence interval (CI): 1.123-13.430, P = 0.032). The 5-year DFS rates in the NACG and ACG groups were 76.3% and 87.5% respectively (P = 0.197). Adjuvant chemotherapy was thus not associated with improved DFS. Furthermore, the number of chemotherapy cycles was not associated with recurrence rate (≤3 cycles vs. > 3 cycles, HR = 0.613, 95% CI: 0.112-3.351, P = 0.572). Conclusion Administration of adjuvant chemotherapy does not improve DFS in patients with stage IC AGCT. Further studies with larger samples involving multi-institutional collaboration are needed to validate new treatment regimens for this disease.